2001
DOI: 10.1074/jbc.m101188200
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Inhibits Cell Cycle Progression and Induces Stabilization of p53 in Bovine Aortic Endothelial Cells

Abstract: Lithium affects development of various organisms and cell fate through the inhibition of glycogen synthase kinase-3␤ and induction of the Wnt/␤-catenin signaling pathway. In this study, we investigated the effects of lithium on primary bovine aortic endothelial cells (BAEC). Lithium treatment of BAEC induced ␤-catenin stabilization but failed to activate the transcriptional activity of the ␤-catenin/T-cell factor complex. Lithium caused a sustained G 2 /M cell cycle arrest without affecting cell viability. Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 68 publications
(94 reference statements)
5
83
1
Order By: Relevance
“…Considerable evidence from previous reports has established that VEGF signaling through Flk-1/KDR/ VEGFR-2 or Flt-1/VEGFR1 induces activation of ERK1/2, p38 MAPK, Akt, phospholipase Cg, and focal adhesion kinase (Abedi and Zachary, 1997;Gerber et al, 1998b;Kroll and Waltenberger, 1997;Mao et al, 2001;Wu et al, 2000). While focal adhesion kinase is associated with cell migration (Lu (Parrizas et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence from previous reports has established that VEGF signaling through Flk-1/KDR/ VEGFR-2 or Flt-1/VEGFR1 induces activation of ERK1/2, p38 MAPK, Akt, phospholipase Cg, and focal adhesion kinase (Abedi and Zachary, 1997;Gerber et al, 1998b;Kroll and Waltenberger, 1997;Mao et al, 2001;Wu et al, 2000). While focal adhesion kinase is associated with cell migration (Lu (Parrizas et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cell cycle distribution showing an increase of cells in G 2 /M phase and a decrease in G 0 /G 1 phase indicated that lithium could lead to a G 2 /M cell cycle arrest ( Figure 3 and Table 1), which is the common characteristic of cell cycle arrest induced by lithium. However, different cell types have their own doses of sensitivity [15,17] . In the report of Mao et al [17] , 5 mmol/L lithium was enough to induce a G 2 /M phase arrest of bovine aortic endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium has been shown to be a specific and noncompetitive inhibitor of GSK-3β activity in vitro [8,9] and in vivo [10] . It has been proved that lithium could promote [11][12][13][14] or inhibit [7,[15][16][17] cell cycle transition and proliferation of some primary cultures or cell lines by inhibiting GSK-3β, depending on the cell type. However, whether lithium influences the growth and proliferation of EC cells remains unknown to date.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, a concept of phosphorylationdependent regulation of p21 Cip1 turnover resembles the mechanism by which GSK-3-mediated phosphorylation triggers both nuclear exit and subsequently the ubiquitin-mediated proteasomal degradation of another regulator of G 1 cell cycle progression, cyclin D (13,25). While preparing this manuscript, Mao et al (26) published that LiCl stabilized p53 and thereby transcriptionally increased p21…”
Section: Herein We Have Investigated the Regulation Of P21mentioning
confidence: 99%